2015
DOI: 10.1016/j.enpol.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The changing landscape of thermal experience and warmth in older people’s dwellings

Abstract: Thermal variations across space affect the use of space within a dwelling. Older people show interest in and understanding of thermal behavior of dwellings. Older people pursue the thermal conditions they desire. Older people take actions to modify the quality of the thermal environment in their house. Changes made to the house may not be solely motivated by thermal comfort concerns. a b s t r a c tThe UK's carbon dioxide reduction policy initiatives often treat environmental conditions in buildings as average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…27 The thermal environment was cited as an important factor in determining what spaces residents would occupy -moving to different lounges or dining rooms, or even different parts of these communal spaces. 28 Thermal comfort considerations were found to have a strong bias towards keeping residents comfortably warm in winter rather than comfortably cool in summer, 7,8,29 with frontline carers often ill-equipped to manage heat effectively in the summer. 30 Some frontline staff identified care home design being a hindrance to keeping the indoor environment cool.…”
Section: Evidence To Datementioning
confidence: 99%
“…27 The thermal environment was cited as an important factor in determining what spaces residents would occupy -moving to different lounges or dining rooms, or even different parts of these communal spaces. 28 Thermal comfort considerations were found to have a strong bias towards keeping residents comfortably warm in winter rather than comfortably cool in summer, 7,8,29 with frontline carers often ill-equipped to manage heat effectively in the summer. 30 Some frontline staff identified care home design being a hindrance to keeping the indoor environment cool.…”
Section: Evidence To Datementioning
confidence: 99%
“…Even less is known about any distinctions between vulnerable and non-vulnerable households, in terms of either the temperatures within their homes, or the ventilation patterns they choose (van Hoof et al, 2010;Tweed et al, 2015;White-Newsome et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, other studies have confirmed that the PMV indices of the elderly were different from those of young adults. 21,39,40 As people aged, their core temperature, metabolic rate, cardiac output, skin blood supply and the density of their sensory epidermal nerve fibres all decrease. 41 These changes definitely affect senior adults’ thermal responses and thermoregulatory systems, which in turn influence their thermal comfort.…”
Section: Discussionmentioning
confidence: 99%